PENGAWASAN OMBUDSMAN TERHADAP PENYELENGGARAAN PELAYANAN PUBLIK PADA MASA PANDEMI CORONA VIRUS DISEASE 2019 (COVID-19) - Inggit Akim (JURNAL AKTA YUDISIA, 2021)
ABSTRACTSupervise the government as the provider of public services to carry out their duties and authorities under applicable regulations. Large-Scale Social Restrictions are restrictions on certain activities in an area suspected of being infected with Corona Virus Disease 2019 (COVID-19), which causes the quality of public services to be disrupted. The Ombudsman has the task of supervising the implementation of shared services organized by state or government officials and private or individual bodies assigned the task of providing services according to minimum service standards as a benchmark for service delivery and assessing the quality of services to the community. The research method used is normative juridical research with a conceptual approach (Statute Approach).The results of this study are large-scale social restriction policies through the Mayor of Tarakan Regulation Number 17 of 2020, restrictions on activities outside the house such as the implementation of learning at schools and/or other educational institutions, Work From Home (WFH), religious movements in houses of worship, activities in public places, social and cultural activities and Mandatory rapid tests for those using Sea and Air transportation modes, and providing social assistance to communities affected by COVID-19. Ombudsman's supervision of public services during the COVID-19 pandemic in Tarakan City, namely by conducting coordination and control and cooperation with state and private officials as well as community or individual organizations, opening an Online Complaint Post for COVID-19 Affected Persons. Also, conduct unannounced checks to improve public services in the City of Tarakan. Based on the supervision, the receipt of reports on suspicion of maladministration and the Ombudsman's investigation results are subject to examination. Suppose it is proven that it has committed maladministration in public services, the Ombudsman of the Republic of Indonesia can take corrective action and provide recommendations/suggestions to state administrators to improve the quality of public services. Keywords: Surveillance; Ombudsman; Public Service; COVID-19 Pandemic